Active edible coatings as postharvest technology to preserve the quality of blackberries = Recubrimientos comestibles activos como tecnología poscosecha para preservar la calidad de moras - Goñi, Maria Gabriela (2023)
Blackberries are fruits of great commercial value, but at the same time highly fragile and with reduced shelflife. Its extreme fragility and susceptibility to mechanical deterioration justifies the need to deepen into technological alternatives that allow prolonging its useful life. The use of edible coatings emerges as a promising alternative to preserve the postharvest quality of blackberries. Natural additives such as antimicrobials, antioxidants, firmness agents or bioactive ingredients can be added into them in order to increase safety and maintain the sensory, nutritional and functional characteristics of minimally processed fruits. The objective of this work was to evaluate the quality of blackberries (Rubus fructicosus var Ouchita) from the first harvest (december) and their behavior during the postharvest, after applying chitosan, alginate and alginate coatings with the addition of vanillin, as an alternative to maintain the quality of the fruits. The first stage of the work was carried out analyzing the fruits at the time of harvest and during 14 days of refrigerated storage without the application of coatings, in order to determine their useful life. In addition, physicochemical and nutritional quality parameters (firmness, soluble solids, titratable acidity, ascorbic acid retention, total polyphenols and antioxidant capacity) were evaluated at 0, 4, 7, 11 and 14 days of storage. Microbiological quality, sensory acceptability and fungal deterioration were also evaluated. In a second stage of the experimental design, the blackberries were treated with different edible coatings and stored under refrigeration (5ºC) to determine their useful life, performing the previously detailed determinations. The results obtained indicated that active edible coatings could be considered as a potential alternative for postharvest preservation that allows maintaining the quality attributes of blackberries and prolonging their marketing period; however, even more research is required to be able to be transferred to fruit and vegetable producers.